Citizenship diplomacy for football supporters of pss sleman and psim yogyakarta to strengthen national identity - Nurgiansah, T Heru; Danial, Endang; Rahmat, Rahmat; Mahpudz, Asep; Suryadi, Karim (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2025)
Conflicts between supporters, provocative actions that exacerbate differences, unsportsmanlike attitudes in accepting match results, excessive fanaticism, hate speech on social media, and intimidation leading to criminal acts are some of the serious problems that must be resolved immediately, especially in football sports in order to create legal certainty as a concrete solution in fostering football supporters. The purpose of this study is to strengthen the National Identity of Football Supporters through the Concept of Civic Disposition and Unity and Diversity so that conflicts between supporters can be resolved. The study was conducted on PSS Sleman and PSIM Yogyakarta Football supporters. This research method uses a qualitative method with a case study approach to answer the main questions regarding the development of civic disposition and strengthening National Identity among football supporters in Yogyakarta. The results of the study state the importance of combining preventive and educational approaches in dealing with supporter conflicts in Indonesia using the concepts of Civic Disposition and Unity and Diversity